2008
DOI: 10.1007/s10557-008-6115-x
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptosis and Mitochondrial Effect of Pioglitazone Preconditioning in the Ischemic/reperfused Heart of Rat

Abstract: Pioglitazone inhibited cardiomyocyte apoptosis and reduced mitochondrial ultrastructure injury and membrane potential loss in the ischemic/reperfused heart of rat. These protective effects of pioglitazone may be related to opening mitochondrial(ATP)-sensitive potassium channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…Supportingly, we found that inhibition of the MEK/ERK pathway abolished the hypoxia-induced increase in ⌬⌿ m . It is well established that reduction or loss of ⌬⌿ m is usually associated with apoptotic processes (10,14,22), whereas maneuvers preventing loss of ⌬⌿ m were shown to protect cells from apoptotic cell death (11,20,39). In this context our findings suggest that hypoxiainduced MEK/ERK activation, leading to phosphorylation and inactivation of the pro-apoptotic molecule Bad, results in a protection of mitochondrial membrane integrity by increasing ⌬⌿ m .…”
Section: Discussionsupporting
confidence: 53%
“…Supportingly, we found that inhibition of the MEK/ERK pathway abolished the hypoxia-induced increase in ⌬⌿ m . It is well established that reduction or loss of ⌬⌿ m is usually associated with apoptotic processes (10,14,22), whereas maneuvers preventing loss of ⌬⌿ m were shown to protect cells from apoptotic cell death (11,20,39). In this context our findings suggest that hypoxiainduced MEK/ERK activation, leading to phosphorylation and inactivation of the pro-apoptotic molecule Bad, results in a protection of mitochondrial membrane integrity by increasing ⌬⌿ m .…”
Section: Discussionsupporting
confidence: 53%
“…and that might have been improved by orally administered pioglitazone. The orally administered pioglitazone-induced angiogenic effect at peri-MI normal zone and/or antiapoptotic effect [32] might be essential for the survival of transdifferentiated cardiomyocytes. Improvement of survival of BM-MSCs in situ might also improve the effect of transplantation of BM-MSCs in this study.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In some recent experimental studies using a rat model, treatment with pioglitazone before myocardial ischemia/ reperfusion reduced myocardial infarct size by attenuating reperfusion injury 34,35…”
Section: Pioglitazone and Myocardial Ischemia/reperfusion Injurymentioning
confidence: 99%